Human Heme Oxygenase Oxidation of 5- and 15-Phenylhemes - Wang, Jingling (2004)
Human heme oxygenase-1 (hHO-1) catalyzes the O2- dependent oxidation of heme to biliverdin, CO, and free iron. Previous work indicated that electrophilic addition of the terminal oxygen of the ferric hydroperoxo complex to the -meso-carbon gives 5-hydroxyheme. Earlier efforts to block this reaction with a 5-methyl substituent failed, as the reaction still gave biliverdin IX . Surprisingly, a 15-methyl substituent caused exclusive cleavage at the -meso- rather than at the normal, unsubstituted -meso-carbon. No CO was formed in these reactions, but the fragment cleaved from the porphyrin eluded identification. We report here that hHO-1 cleaves 5-phenylheme to biliverdin IX and oxidizes 15- phenylheme at the -meso position to give 10-phenylbiliverdin IX . The fragment extruded in the oxidation of 5-phenylheme is benzoic acid, one oxygen of which comes from O2 and the other from water. The 2.29- and 2.11-Å crystal structures of the hHO-1 complexes with 1- and 15-phenylheme, respectively, show clear electron density for both the 5- and 15-phenyl rings in both molecules of the asymmetric unit. The overall structure of 15-phenylheme-hHO-1 is similar to that of heme-hHO-1 except for small changes in distal residues 141–150 and in the proximal Lys18 and Lys22. In the 5-phenylhemehHO-1 structure, the phenyl-substituted heme occupies the same position as heme in the heme-HO-1 complex but the 5-phenyl substituent disrupts the rigid hydrophobic wall of residues Met34, Phe214, and residues 26–42 near the -meso carbon. The results provide independent support for an electrophilic oxidation mechanism and support a role for stereochemical control of the reaction regiospecificity.